Pemberdayaan Kesehatan Remaja : Edukasi Bahaya Rokok Elektrik bagi Siswa SMA Negeri 2 Tegal - Susanto, Agus; Mahardika, Muladi Putra; Purwantiningrum, Heni (Jurnal Pengabdian UNDIKMA, 2023)
The community service program aims to increase awareness and knowledge about the dangers of e-cigarettes and their impact on adolescent health. The implementation of this service was carried out using the interactive counseling method. The targets of this activity were 10th and 11th-grade students of SMA Negeri 2 Tegal. The evaluation instrument of this activity used pre-test and post-test and was analyzed descriptively. The results of this community service activity showed an increase in student knowledge by 4.68 after participating in counseling activities. The increase in participants' knowledge included knowledge about the safety of e-cigarettes and the chemical content of e-cigarettes. In addition, knowledge about the dangers of e-cigarettes for health, especially for the respiratory system, brain health, heart health, and lung health.